2022
DOI: 10.3389/fgene.2022.879468
|View full text |Cite
|
Sign up to set email alerts
|

Genetic liability to asthma and risk of cardiovascular diseases: A Mendelian randomization study

Abstract: Background and Aims: Epidemiological studies have suggested positive associations between asthma and the risk of cardiovascular diseases (CVDs). However, causality remains inconclusive. We aim to explore the causal associations between asthma and CVDs risk using the Mendelian Randomization (MR) approach.Methods: We obtained summary-level data for eight CVDs [including atrial fibrillation (AF), coronary artery disease (CAD), heart failure (HF), stroke, ischemic stroke, large artery stroke, small vessel stroke, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Some studies demonstrated that adult-onset asthma was associated with CAD, especially in females ( 25 , 26 ), and the potential mechanism may involve systemic inflammation and cellular immunity. However, some bioinformatics analyses (such as MR) found that asthma was a causal factor for atrial fibrillation and heart failure, but not for CAD ( 27 , 28 ). Therefore, more research is needed to explore the relationship between asthma and coronary atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated that adult-onset asthma was associated with CAD, especially in females ( 25 , 26 ), and the potential mechanism may involve systemic inflammation and cellular immunity. However, some bioinformatics analyses (such as MR) found that asthma was a causal factor for atrial fibrillation and heart failure, but not for CAD ( 27 , 28 ). Therefore, more research is needed to explore the relationship between asthma and coronary atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…106 A causal association between genetic liability to mood instability and 21 to 45% higher odds of acute coronary syndrome (ACS), CHD, DVT, or pulmonary embolism was partially mediated by dyslipidemia, body mass index, smoking, and depression. 107 Individuals with unstable mood may experience acute episodes of depressive mood and anger, both of which can act as triggers for ACS. 28,108 Low education level was causally associated with an increased risk of CHD, MI, ischemic stroke, PAD, DVT, and VTE, potentially mediated by cardiometabolic and lifestyle factors.…”
Section: Evidence From Mendelian Randomization Studiesmentioning
confidence: 99%
“…Studies have shown that age at rst birth (AFB) is associated with many disorders [9][10][11][12][13], and that women who give birth earlier are more likely to be at risk of poor mental health and those who give birth later are more psychologically advantaged, but there are only a few studies that support the link between early and late childbearing and depression and there are contradictions [14,15]. Previous studies by Mirowsky J et al showed that the association between AFB and depression presented a U-shaped parabolic relationship in women, with a minimum around the age of 30 years [16].…”
Section: Introductionmentioning
confidence: 99%